Applications of Metal‐Organic Frameworks in Water Treatment: A Review. Issue 11 (8th December 2021) - Yang, Feiyu; Du, Meng; Yin, Kailiang; Qiu, Ziming; Zhao, Jiawei; Liu, Chunli; Zhang, Guangxun; Gao, Yajun; Pang, Huan
Abstract: The ever‐expanding scale of industry and agriculture has led to the gradual increase of pollutants (e.g., heavy metal ions, synthetic dyes, and antibiotics) in water resources, and the ecology and wastewater are grave problems that need to be solved urgently and has attracted widespread attention from the research community and industry in recent years. Metal‐organic frameworks (MOFs) are a type of organic–inorganic hybrid material with a distinctive 3D network crystal structure. Lately, MOFs have made striking progress in the fields of adsorption, catalytic degradation, and biomedicine on account of their large specific surface and well‐developed pore structure. This review summarizes the latest research achievements in the preparation of pristine MOFs, MOF composites, and MOF derivatives for various applications including the removal of heavy metal ions, organic dyes, and other harmful substances in sewage. Furthermore, the working mechanisms of utilizing adsorption, photocatalytic degradation, and membrane separation technologies are also briefly described for specific pollutants removal from sewage. It is expected that this review will provide inspiration and references for the synthesis of pristine MOFs as well as their composites and derivatives with excellent water treatment performance. Abstract : Design and synthesis of 1D metal‐organic frameworks (MOFs), 2D MOF nanosheets, 3D MOFs, MOF composites, and MOF derivatives for various environmental protection applications are reviewed. Working mechanisms of utilizing adsorption, photocatalytic degradation, and membrane separation technologies for heavy metal ions, organic dyes, antibiotic drugs, and other specific pollutants removal from sewage are briefly introduced.